2016
DOI: 10.1017/pab.2015.50
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology and habitat preferences of top predators from two Miocene carnivore-rich assemblages

Abstract: Carnivore-rich fossil sites are uncommon in the fossil record and, accordingly, provide valuable opportunities to study predators from vantages that are rarely applied to ancient faunas. Through stable isotopes of carbon and a Bayesian mixing model, we analyze time-successive (nearly contemporaneous), late Miocene carnivoran populations from two fossil sites (Batallones-1 and Batallones-3) from central Spain. Stable isotopes of carbon in tooth enamel provide a reliable and direct methodology to track ancient d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…In the case of BAT, we have included the ursid Indarctos arctoides in the predator analysis since M. S. Domingo et al . () observed that the tooth enamel δ 13 C offset between BAT‐3 Indarctos and BAT‐3 herbivore (i.e. Δδ 13 C Indarctos ‐herbivore ) was −1.42‰, comparable to the tooth enamel Δδ 13 C carnivore–herbivore of value −1.3‰, determined by Clementz et al .…”
Section: Methodssupporting
confidence: 57%
See 3 more Smart Citations
“…In the case of BAT, we have included the ursid Indarctos arctoides in the predator analysis since M. S. Domingo et al . () observed that the tooth enamel δ 13 C offset between BAT‐3 Indarctos and BAT‐3 herbivore (i.e. Δδ 13 C Indarctos ‐herbivore ) was −1.42‰, comparable to the tooth enamel Δδ 13 C carnivore–herbivore of value −1.3‰, determined by Clementz et al .…”
Section: Methodssupporting
confidence: 57%
“…This is supported by statistical tests that reveal no differences in their isotopic values when comparing BAT sites (Domingo, M. S. et al . ). These fossil sites show subtle differences in age (0.30 myr at most, with BAT‐10 being the oldest and BAT‐3 the youngest) as evidenced by micro‐mammal biochronology (López‐Antoñanzas et al .…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Full-size  DOI: 10.7717/peerj.8767/ fig-1 Palaeoecological, palaeoenvironmental and taphonomical studies carried out at Batallones Butte (Antón & Morales, 2000;Domingo et al, 2011Domingo et al, , 2013aDomingo et al, , 2013bDomingo et al, , 2016 have treated the upper and lower part of the hourglass-shaped cavities separately based on their different depth and their different taxonomical composition (herbivores vs. carnivores, respectively). Due to the challenges posed by the structure of the deposits that filled the Batallones Butte cavities, such as lateral facies changes, deformations, depositional asymmetries, collapse structures, slickensides and/or local tilting typical of cave deposits (Calvo et al, 2013), geological sub-levels have not been identified within each of these parts.…”
Section: Introductionmentioning
confidence: 99%